The Road to Bribery and Corruption - Köbis, Nils C.; van Prooijen, Jan-Willem; Righetti, Francesca; Van Lange, Paul A. M. (Psychological Science, 2017)
Major forms of corruption constitute a strong threat to the functioning of societies. The most frequent explanation of how severe corruption emerges is the slippery-slope metaphor-the notion that corruption occurs gradually. While having widespread theoretical and intuitive appeal, this notion has barely been tested empirically. We used a recently developed paradigm to test whether severely corrupt acts happen gradually or abruptly. The results of four experimental studies revealed a higher likelihood of severe corruption when participants were directly given the opportunity to engage in it (abrupt) compared with when they had previously engaged in minor forms of corruption (gradual). Neither the size of the payoffs, which we kept constant, nor evaluations of the actions could account for these differences. Contrary to widely shared beliefs, sometimes the route to corruption leads over a steep cliff rather than a slippery slope.